Strategi Komunikasi Pemasaran Pariwisata Danau Toba Oleh Badan Pelaksana Otorita Danau TOba (BPODT) Dalam Pengembangan Branding â€œLAKE TOBA CALDERA OF KINGSâ€ - Sagala, Wiranda Tappang (Talenta Publisher, 2023)
This research was conducted to analyze the marketing communication strategy of Lake Toba tourism and the obstacles of the Lake Toba Authority (BPODT) in developing the